(untitled) (Indian Journal of Animal Production and Management, 2025)
The study was conducted to evaluate the efficiency and productivity of hand milking versus machine milking methods in Kankrej cattle at the Livestock Research Station, Kamdhenu University, Gujarat. Twenty lactating cows were selected and divided into two groups to compare milking time, yield, and milk composition. Machine milking was found to be more efficient with significantly higher milk yield and reduced milking time while maintaining comparable milk quality parameters. These findings support the adoption of machine milking in Kankrej cattle for improved dairy farm efficiency.